'Globalizing the Local, Localizing the Global': Writing Space in the Arab Gulf Region. (4th May 2021) - Ait Oukhzame, El Mehdi
Abstract : The United Arab Emirates (UAE) and Qatar are taking the lead in the urbanization boom that is drastically transforming the spatial fabric of the Arab Gulf region. Embedded in the ambitious urban development projects launched by the UAE and Qatar is an endeavour to 'bring the world to the Arab Gulf region'. To this end, these two states are engaged in a process of collecting and borrowing antique objects and canonized artefacts, as well as reproducing and duplicating some internationally celebrated architectural sites and spaces. While some consider these projects to be 'part of strategies to prepare for the post-oil era', others hold that 'Arab Gulf States aim to strengthen or … creatively (re)construct identitarian patterns'.1 It can be argued that Arab Gulf cities should be looked at as 'political actors' due to 'the functions they fulfill as spatial command posts for globalized capitalism'.2 The production and organization of social space, in this sense, cannot be seen as a 'dead' or passive category with no influence over various dimensions of lived experience, including thought, politics and economy. Juxtaposing the UAE's and Qatar's urbanization projects with the nineteenth-century phenomenon of world exhibitions and fairs, this article takes the Louvre Abu Dhabi and Villaggio Mall as case studies to investigate the modalities of knowledge generated through processes of cultural and spatial (re)production and the impact of the latter on the construction of personhood and lived experience in the Arab Gulf region.